Radon exposure: a major cause of lung cancer. (2nd September 2019) - Lorenzo-González, María; Torres-Durán, María; Barbosa-Lorenzo, Raquel; Provencio-Pulla, Mariano; Barros-Dios, Juan Miguel; Ruano-Ravina, Alberto
ABSTRACT: Introduction : Lung cancer is the most important cause of cancer mortality. It is a multifactorial disease with multiple risk factors, including residential radon exposure. Areas covered : The aim of this paper was to review the epidemiology of residential radon exposure and its impact on lung cancer risk. While tobacco is the main risk factor of lung cancer, residential radon is the first cause in never-smokers and the second in ever-smokers. Moreover, the synergistic effect between tobacco consumption and radon exposure should be considered. However, the biological mechanism by which radon and its decay products induce lung cancer is not entirely known. Expert opinion : Residential radon is usually neglected by clinicians. In fact, no lung cancer risk score (predicting incidence or mortality) includes radon as a variable. Further studies are needed to find out the molecular pathways of radon that cause lung cancer and whether this radioactive gas is also involved in the development of other diseases other than lung cancer. There is a clear need to increase awareness among administrations, health professionals and the general population in order to take the necessary measures to reduce this harmful exposure, particularly in radon-prone areas.